Tolerance Level of S4 Corn Lines to Drought Stress in Dry Land - I Wayan Sudika; I Wayan Sutresna; Dwi Ratna Anugrahwati; I Gusti Putu Muliarta Aryana (Jurnal Penelitian Pendidikan IPA, 2024)
Selfing is the initial step to form hybrid varieties. Selfing has been carried out for four generations and 29 S4 lines have been obtained. All lines have been tested for their tolerance level to drought stress in dry land. The purpose of the study was to determine the tolerance level of S4 lines of corn plants to drought stress in dry land. Experimental methods with field trials were used for the test. And the correlation between characters and ISC values. The design used was a randomized block design at each stress level. Determination of the tolerance level used the observation parameter of the results (dry seed weight per plant) under mild stress conditions and normal conditions. The tolerance level to drought stress was measured from the Stress Sensitivity Index (ISC) value. The results showed that three S4 lines were tolerant to drought stress, namely lines S4.7, S4.15 and S4.24. Nine S4 lines have moderately tolerant category, namely lines S4.1, S4.3, S4.8, S4.12, S4.13, S4.14, S4.21, S4.26 and S4.29; the rest are classified as sensitive. The yield have a high negative correlation with the ISC value; the weight of dry cobs harvested per plant has a moderate negative correlation. The three tolerant lines can be used for the formation of S5 lines.